Evaluation of CHSE-Based Homestay Business Management in Ubud Tourism Area - Putri, Ida Ayu Karina; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism; Volume 8 Number 2 (September 2021)DO - 10.24922/eot.v8i2.78277, 2021)
The Bali Provincial Government together with the Indonesian Ministry of Tourism and Creative Economy in the recovery of tourism in the new normal era, by implementing the certification of cleanliness, health, safety and environmental sustainability also known as CHSE in the management of tourism business including homestay business in Ubud Tourism Area. This research aims to evaluate homestay business management during Covid-19 pandemic and to evaluate tourism recovery efforts in Ubud Tourism Area. The research was conducted by observing 30 homestays in the Ubud Tourism Area. Data analysis technique was using qualitative and quantitative descriptive analysis. The results showed homestay business management in the Ubud Tourism Area has already a good implementation of CHSE management. Tourism recovery efforts in Ubud Tourism Area were ‘We Love Bali’ campaign, the establishment of a green zone and socialization for strengthening the destination organization management-governance destination that have been well implemented.